(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In order to enhance the quality of life for the majority of people, education is the most importantfactor. It is crucial for the country’s rapid growth to cultivate all of its available human resources. Allpeople are valuable assets that contribute to the well-being of the nation. To be nurtured and cared forwith kindness and care accompanied by dynamism. Today’s culture has required women to fill a variety ofpositions, and they’ve done just that. They continue to take care of the household and their loved oneswhile also working outside the home and pursuing their own hobbies and passions. Teacher has theoption of seeing these roles as challenges or threats. A sense of powerlessness and lack of control canlead to stress and exhaustion for teachers who have to fulfill these duties. Stress occurs when peoplebelieve they are unable to handle the demands placed on them or dangers to their well-being. HansSeley, the father of stress research, was the first to define stress. Stress, according to him, is thebody’s nonspecific reaction to a demand. Basically, he’s saying that your body responds in a specificway to any stressors that come your way.